2013
DOI: 10.1371/journal.pmed.1001363
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Mobile-Health Technologies to Improve Health Care Service Delivery Processes: A Systematic Review and Meta-Analysis

Abstract: Caroline Free and colleagues systematically review controlled trials of mobile technology interventions to improve health care delivery processes and show that current interventions give only modest benefits and that high-quality trials measuring clinical outcomes are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
756
0
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 971 publications
(782 citation statements)
references
References 54 publications
15
756
0
11
Order By: Relevance
“…For example, new private philanthropic support for develop ment has expanded, 67 logistics and information and computer technology businesses have emerged, and m-health (health services using mobile technologies) initiatives have fl ourished, with benefi ts to service delivery and care management. 68 New forms of public-private partnerships have emerged in the health sector from which lessons can be learned about how to identify a balance of interests and incentives among partners. 69 As a result of these many public and privatesector intersections, the interest of the public sector towards business involvement in undernutrition eff orts has increased substantially.…”
Section: Private Sector Engagement: Maximising Potential and Managingmentioning
confidence: 99%
“…For example, new private philanthropic support for develop ment has expanded, 67 logistics and information and computer technology businesses have emerged, and m-health (health services using mobile technologies) initiatives have fl ourished, with benefi ts to service delivery and care management. 68 New forms of public-private partnerships have emerged in the health sector from which lessons can be learned about how to identify a balance of interests and incentives among partners. 69 As a result of these many public and privatesector intersections, the interest of the public sector towards business involvement in undernutrition eff orts has increased substantially.…”
Section: Private Sector Engagement: Maximising Potential and Managingmentioning
confidence: 99%
“…It is also inherently evident that most of the studies reviewed in this paper were undertaken over shorter periods of time (between 2 years and 4 days). Whereas this is a limitation beyond this paper, it is a calling for longitudinal studies and long term programmatic efforts that would provide more detailed evidence [40][41][42][43][44][45][46][47][48][49][50][51][52].…”
Section: Resultsmentioning
confidence: 99%
“…These include inconsistencies in the kinds of smartphones used by community healthcare workers that lead to poor imaging of the condition, which in turn, causes difficulties in assessing and diagnosing patients (Asgary et al, 2016;Free et al, 2013). Additionally, a systematic review of mHealth interventions on community healthcare workers found that most interventions were overwhelmingly focused on the context of the global North, with many of them having limited success outside of that space (Free et al, 2013). Missing from these studies are the cultural contexts, and more specifically, the cultural contexts of Asia.…”
Section: Mhealth and Communitymentioning
confidence: 99%